Brain Metastases: quest on primary site - Jagdish Arvindbhai Prajapati; Ashini Hemal Shah; Priti Pinakin Trivedi; Amisha Jigar Gami; Vibha Rasesh Vyas; Jahnavi Sanjay Gandgi (Gandhi) (Tropical Journal of Pathology and Microbiology, 2019)
Background: Secondaries of brain (Brain metastases, BM) are most common central nervous system (CNS) tumors and it may be initial manifestation of systemic malignancies. Histomorphology of brain metastatic tumors along with immunohistochemistry (IHC) will helpful in the detection of unknown primary site (UPS) of brain metastases.Aim: To evaluate unknown primary site of brain metastases with help of immunohistochemistry.Material and Method: This study was conducted at the department of onco-pathology of our institute. Five years data from 2014 to 2018 were obtained from online Laboratory Information System (LIS), department of onco-pathology of our institute. IHC was performed on basis of histomorphology.Results: Total 128 brain metastatic tumors were retrieved. Of which the present study have applied IHC on 107 cases and in remaining 21 cases, systemic malignancies were already diagnosed. Out of 107 cases, primary site was detected in 92.53% cases (n=99) and in 7.47% cases (n = 8), not able to detect primary site even after IHC. Lung was the most common primary site detected (n = 73) followed Gastrointestinal tract (GIT, n = 9).Conclusion: Lung followed by breast are the most common primary malignancies for secondaries of brain (BM). Systemic approach using immunohistochemistry is really helpful in detection of unknown primary site of secondaries of brain (BM).